Interesting Probiotic Bacteria Other Than the More Widely Used Lactic Acid Bacteria and Bacilli in Finfish - Ringø, Einar; Li, Xuemei; Doan, Hien van; Ghosh, Koushik (Frontiers in Marine Science, 2022)
Growing demands stimulate the intensification of production and create the need for practices that are both economically viable and environmentally sustainable. As European Union banned the use of antibiotics in production in 2003, several alternative treatments have been suggested, including probiotics. The first probiotic study in aquaculture was published in 1986, and since then probiotics have been considered as a beneficial tool in this industry. Today current evidence suggests that administration of certain probiotic strains might be able to enhance growth rate, improve the welfare of different fish species by modulating gut microbiota, improve physiological functions, such as metabolism, digestion, immunity, stress tolerance, intestinal histology, and disease resistance. Even though lactic acid bacteria and Bacillus spp. are the most frequently used probiotics in aquaculture, numerous studies have been published on other interesting probiotics. Therefore, the purpose of this paper is to summarize, comment, and discuss the current knowledge related to the effects of Aeromonas, Aliivibrio, Alteromonas, Arthrobacter, Bifidobacterium, Brochothrix, Clostridium, Enterovibrio, Kocuria, Microbacterium, Micrococcus, Paenibacillus, Phaeobacter, Pseudoalteromonas, Pseudomonas, Rhodococcus, Rhodopseudomonas, Rhodosporidium, Roseobacter, Shewanella and Vibrio as probiotics in finfish aquaculture, and present general information on their presence in the gastrointestinal tract of finfish. Moreover, some considerations for future studies are also indicated.